Field notes contributed by Dennis L. Carter, December 2, 1991 - Carter, Dennis L.et al (1991)
List of birds and locations contributed by Dennis L. Carter. The field notes include details on several species. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1991. Epson - sheet feed/flatbed